Involvement of Cannabinoid Signaling in Vincristine-Induced Gastrointestinal Dysmotility In The Rat - Vera, Gema; López-Pérez, Ana E.; Uranga, Jose A.; Girón, Rocío; Martín-Fontelles, Mª Isabel; Abalo, Raquel (Frontiers in Pharmacology, 2017)
Background. In different models of paralytic ileus, cannabinoid receptors are overexpressed and endogenous cannabinoids are massively released, contributing to gastrointestinal dysmotility. The antitumoral drug vincristine depresses gastrointestinal motility and a similar mechanism could participate in this effect. Therefore, our aim was to determine, using CB1 and CB2 antagonists, whether an increased endocannabinoid tone is involved in vincristine-induced gastrointestinal ileus. Methods. First, we confirmed the effects of vincristine on the gut mucosa, by conventional histological techniques, and characterized its effects on motility, by radiographic means. Conscious male Wistar rats received an intraperitoneal injection of vincristine (0.1-0.5 mg/kg), and barium sulfate (2.5 ml; 2g/ml) was intragastrically administered 0, 24 or 48 h later. Serial X-rays were obtained at different time-points (0-8 h) after contrast. X-rays were used to build motility curves for each gastrointestinal region and determine the size of stomach and caecum. Tissue samples were taken for histology 48 h after saline or vincristine (0.5 mg/kg). Second, AM251 (a CB1 receptor antagonist) and AM630 (a CB2 receptor antagonist) were used to determine if CB1 and/or CB2 receptors are involved in vincristine-induced gastrointestinal dysmotility. Key results: Vincristine induced damage to the mucosa of ileum and colon and reduced gastrointestinal motor function at 0.5 mg/kg. The effect on motor function was particularly evident when the study started 24 h after administration. AM251, but not AM630, significantly prevented vincristine effect, particularly in the small intestine, when administered thrice. AM251 alone did not significantly alter gastrointestinal motility. Conclusions. The fact that AM251, but not AM630, is capable of reducing the effect of vincristine suggests that, like in other experimental models of paralytic ileus, an increased cannabinoid tone develops and is at least partially responsible for the alterations induced by the antitumoral drug on gastrointestinal motor function. Thus, CB1 antagonists might be useful to prevent/treat ileus induced by vincristine.